Adverse Infant Outcomes Associated with Discordant Gestational Age Estimates. Issue 6 (23rd August 2016) - Morken, Nils‐Halvdan; Skjærven, Rolv; Richards, Jennifer L.; Kramer, Michael R.; Cnattingius, Sven; Johansson, Stefan; Gissler, Mika; Dolan, Siobhan M.; Zeitlin, Jennifer; Kramer, Michael S.; ,
Abstract: Background: Gestational age estimation by last menstrual period (LMP) vs. ultrasound (or best obstetric estimate in the US) may result in discrepant classification of preterm vs. term birth. We investigated whether such discrepancies are associated with adverse infant outcomes. Methods: We studied singleton livebirths in the Medical Birth Registries of Norway, Sweden and Finland and US live birth certificates from 1999 to the most recent year available. Risk ratios (RR) with 95% confidence intervals (CI) by discordant and concordant gestational age estimation for infant, neonatal and post‐neonatal mortality, Apgar score <4 and <7 at 5 min, and neonatal intensive care unit (NICU) admission were estimated using generalised linear models, adjusting for maternal age, education, parity, year of birth, and infant sex. Results were presented stratified by country. Results: Compared to infants born at term by both methods, infants born preterm by ultrasound/best obstetric estimate but term by LMP had higher infant mortality risks (range of adjusted RRs 3.9 to 7.2) and modestly higher risks were obtained among infants born preterm by LMP but term by ultrasound/best obstetric estimate (range of adjusted RRs 1.6 to 1.9). Risk estimates for the other outcomes showed the same pattern. These findings were consistent across all four countries. Conclusions: Infants classified as preterm by ultrasound/best estimate, but term by LMP have consistently higher risks of adverse outcomes than those classified as preterm by LMP but term by ultrasound/best estimate. Compared with ultrasound/best estimate, use of LMP overestimates the proportion of births that are preterm.